Pengaruh Strategi Komunikasi Melalui Media Digital Linkedin Terhadap Kepuasan Konsumen Jethro - Aldino Yazied Zidane; Mareta Puri Rahastine (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This research aims to analyze the influence of digital communication strategies through LinkedIn on customer satisfaction at JETHRO. A quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4 software was applied. Data were collected from 49 respondents who interacted with JETHRO’s official LinkedIn account. The results show a positive and significant effect of digital communication strategies on customer satisfaction (path coefficient = 0.910; t = 38.767; p = 0.000; R² = 0.828). Indicators such as message clarity, content creativity, audience interaction, and message consistency play dominant roles in enhancing satisfaction. The findings reinforce the Uses and Gratifications Theory and Integrated Marketing Communication framework as conceptual bases for professional digital communication effectiveness.